Study of the word «America» in the story «Una carta de Indias» - Castillo Brückmann, Claudio Arturo (2021)
The aim is to show how a word can have different origins and that everything we know about it can be wrong, or how a misinterpretation can make a word have a great meaning, as Ricardo Palma explains in the story «Una carta de Indias». In it he describes how a small mistake and lack of knowledge can make a word not exactly what we think it is.